ARBOVIROSIS: EPIDEMIOLOGY AND HEALTH CARE - Carolina Salustino dos Santos, Maria; Victor Assis Eloy, Allan; Karine de Assunção Almeida, Anne; Allyson Gomes Ferreira, Jefferson; Claudino do Nascimento, Nathalia; Evelly da Silva Olanda, Debora; Fernandes Filgueiras, Mateus; Elivania da Silva, Maria; Costa Soares Silva, Talita; Casado de Freitas Silva, Rosany; Janayna Mota Duarte Beserra, Hebe; de Araújo Evangelista, Wanessa; et al. (Health and Society, 2022)
Arboviruses are diseases caused by viruses and transmitted by contaminated saliva of hematophagous arthropods during blood meal. The objective is: to analyze scientific productions on the subject of epidemiology and collective care in the context of arboviruses. Study of the integrative, descriptive, exploratory and qualitative review modality. Data collection took place in August, 2022, in the following scientific databases: Latin American and Caribbean Literature on Health Sciences (LILACS); Online Scientific Electronic Library (SciELO); Medical Literature Review (MEDLINE/PUBMED); Web Of Science and Google Scholar. To carry out the search effectively, the Health Sciences Descriptors (DeCS) were defined, which are: Arboviruses; Caution; Epidemiology; Health. The steps established by PRISMA were followed. 07 scientific productions on the subject were gathered. Studies from the year 2022 predominated, in which all of them addressed various aspects related to environmental health, from the symptoms of the disease to its collective impact.